One but not two grandmothers increased child survival in poorer families in west Bohemian population, 1708–1834. (24th July 2021) - Havlíček, Jan; Tureček, Petr; Velková, Alice
Abstract: Human childrearing is characterized by cooperative care and grandmothers are usually the most prominent alloparents. Nevertheless, it has been argued that limited resources may intensify competition among kin. The effect of grandmothers' presence on child survival may thus crucially depend on the family's socioeconomic status. We evaluate the impact of grandmothers' presence on child survival using a large historical dataset from eighteenth to nineteenth-century western Bohemia ( N = 6880) and assess the effects of socioeconomic status. We employed a varying effects model conditioned on relatedness between individuals because of possible genetically transmitted benefits. Proportional hazards showed that grandmothers had little or no impact on child survival in families of high and medium socioeconomic status (farmers and cottagers, respectively), whereas in families with the lowest socioeconomic status (lodgers), grandmothers' presence increased the survival probability of children up to five years of age. The beneficial effect of grandmaternal care was strongest between the first and second years of life. Importantly, though, in families with low socioeconomic status, we also observed lower survival chances of children when both grandmothers lived in the same village. These findings suggest that the balance between kin cooperation in childrearing and competition over resources may depend on resource availability. Abstract : Our study shows that grandmother's presence increases child survival in economically challenged families, but not in families with higher socioeconomic status. Importantly, though, in families with low socioeconomic status, we also observed lower survival chances of children when both grandmothers were present. Thus, if the number of kin in a poor family increases, competition prevails. Our study thus provides insight into delicate balance between cooperation and competition in cooperative breeding.